Issues Regarding Management of Machining Tools, Parts and Sub-Assemblies in Flexible Manufacturing Cells - Avram, Florin; Birouaș, Flaviu; Nilgesz, Arnold; Mihalca, Vlad Ovidiu (Recent Innovations in Mechatronics, 2018)
This paper will be presenting the issues regarding management of machining tools, parts and sub-assemblies in the industrial environment present in flexible manufacturing cells, flexible manufacturing systems or flexible manufacturing multi-systems. In modern the factory environment, management plays vital role in assuring a quality on demand, cost effective and timely production planning. Without proper management performance is not guaranteed or controlled in a manufacturing cell system.